A Concept of Two Authors: Commons and Williamson on Transactions - Guedes, Sebastião Neto Ribeiro [UNESP]; Jeronimo, Rodrigo Constantino [UNESP] (SAGE Publications, 2021)
The idea of transactions in social sciences was conceived by John Rogers Commons in the beginning of the 1920s, representing a mental instrument capable of describing capitalism and its peculiarities. On the other hand, Oliver Williamson’s approach in late 1970s reduced the concept to the mere transfer of goods and services in institutions that are or are not guided by the price system. The aim of this article is to present the characteristics of these two different approaches to the concept of transactions, evidencing the role of epistemological aspects and investigative purposes (referred to relevant research context and problem originated in it) as the causes of its metamorphosis. John Commons’ effort to build up a concept not only capable of transcending the idea of exchange but also of giving a totalising perspective to the interpretation of capitalism is emptied in Williamson’s appropriation of the term. By utilising Commons’ conception of transactions and trying to subsume it to his ‘general theory of transaction costs’, Williamson limits its scope and meaning, adjusting it without producing rupture with the neoclassical economy. This article tries to catch the vicissitudes of this concept found in both authors. JEL: B15, B25, B31.
Keywords: Institutional economics; John R. Commons; Oliver Williamson; transactions